HOMESCHOOLING, ALTERNATIF PENDIDIKAN HUMANISTIK (Studi Kasus Pembelajaran pada Pendidikan Alternatif Qaryah Thayyibah Kalibening, Salatiga, Jawa Tengah) - Siti Mumun Muniroh (Jurnal Forum Tarbiyah, 2009)
Homeschooling or home school is one of the alternatives in dealing with education issues in Indonesia . Through the learning process which is held at home and with a variety of learning methods, it will be able to create a more pleasant atmosphere and create a more creative and independent students. They are more free in expressing their works and make them dependent on others, because basically the students have a tendency and basic needs to develop its potential as much as possible. One of the home school models in Indonesia is an alternative school named Qaryah Thayyibah in the village of Kalibening Salatiga . The school system offers unique and more liberating learning methods. Parents of students from these schools do not need to spend huge money to get an education because the school is a community-based school.